2000
DOI: 10.1042/ba20000047
|View full text |Cite
|
Sign up to set email alerts
|

High‐level synthesis of human prolactin in Chinese‐hamster ovary cells

Abstract: Two eukaryotic human prolactin (hPRL) expression vectors, based on a selectable dihydrofolate reductase (dhfr) marker, were used to transfect dhfr(-) Chinese- hamster ovary (CHO) cells. One vector, p658-hPRL, contains the hepatitis-B virus-X cDNA coding for a viral transactivator and sequences mediating dhfr mRNA degradation. The other, pEDdc-hPRL, carries the encephalomyocarditis virus leader sequence coupled to hPRL cDNA to provide high-level protein expression, possibly via a mechanism of internal translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
12

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
1
15
0
12
Order By: Relevance
“…The clone expressing hPRL, derived from CHO dhfr -cells (DUKX-B11) that had been transfected with the vector pEDdc-hPRL, was obtained in our Laboratory (Soares et al, 2000). Cells were thawed into T-flasks (75 cm 2 , from Corning Costar Corporation, Cambridge, MA) containing ␣-MEM with l-glutamine and without ribonucleosides and deoxyribonucleosides, supplemented with 10% dialyzed fetal bovine serum (dFBS), 40 g ml −1 gentamycin, 4 g l −1 glucose and 100 nM methotrexate.…”
Section: Cell Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…The clone expressing hPRL, derived from CHO dhfr -cells (DUKX-B11) that had been transfected with the vector pEDdc-hPRL, was obtained in our Laboratory (Soares et al, 2000). Cells were thawed into T-flasks (75 cm 2 , from Corning Costar Corporation, Cambridge, MA) containing ␣-MEM with l-glutamine and without ribonucleosides and deoxyribonucleosides, supplemented with 10% dialyzed fetal bovine serum (dFBS), 40 g ml −1 gentamycin, 4 g l −1 glucose and 100 nM methotrexate.…”
Section: Cell Cultivationmentioning
confidence: 99%
“…Unfortunately, the physiological significance of this isoform has not yet been well elucidated, even though it has been postulated that hPRL glycosylation might possibly modulate the bioactivity of the circulating pool of the hormone, perhaps by selectively down-regulating PRL action at individual target tissues (Sinha, 1995;Freeman et al, 2000;Goffin et al, 2002). For these reasons, we and others believe that this and other prolactin variants are needed in purified and characterized form in order to develop proper physiological and clinical studies directed towards the understanding of the more than 300 separate actions of this hormone, whose receptor distribution has been defined as being "quasi-ubiquitous" (Young et al, 1990;Price et al, 1995;Sinha, 1995;Freeman et al, 2000;Soares et al, 2000;Goffin et al, 2002). Impetus for the present investigation was provided by the work of Shelikoff et al (1994), who demonstrated that the addition of a protein synthesis inhibitor (cycloheximide) to C127 cell culture increased recombinant hPRL glycosylation site occupancy.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The GCR cDNA was cloned into the pED dicistronic expression vector, which is commonly used to obtain high-expression levels of heterologous proteins in mammalian cells [4547], and positive clones were isolated and amplified with increasing MTX concentration up to 700 nM MTX. Probably due to the inability of the transfected cells to further amplify the dhfr gene [28], higher concentration of MTX (1200 nM) caused cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Although the highest productivity achieved for secreted GCR was calculated as 5.14 pg/cell/day, higher expression levels have been reported for other recombinant proteins in CHO cells [45, 47]. Here, it should be taken into account the fact that GCR is a membrane-associated glycoprotein secreted at low level or rather not secreted under natural conditions [37].…”
Section: Discussionmentioning
confidence: 99%